A szociális és szolidáris gazdaság csírái a magyarországi vidéki térségekben (Seeds of Social and Solidarity Economy in Hungarian Rural Areas) - Éva Fekete (DETUROPE)
The social and solidarity economy (SSE) is an emerging sector of the European economies. It’s importance is demonstrated by millions of employees and significant share of GDP. In recognition of its perceptivity, ministries dedicated to SSE have been established in many countries. However, there is a lively debate about on the definition of SSE itself. Opinions on the role of employment, the relations to governments and attitudes to competitiveness differ from each other. In the first part of my paper a clarification of the conceptual issues will be summarized. After that we may follow our investigations on SSE in two directions. First, we will see the special appearance of the SSE in rural areas and then the situation in Hungary will be presented. As an intersection of this two lines, SSE initiatives in the Hungarian rural areas will be discussed. We can speak about the role of the social land programs, the cooperatives, the LEADER groups and the “START” public work in building SSE in the Hungarian rural space.